Prognostic relevance of ARFI elastography in comparison to liver histology and the FIB-4 score - Klüppel, Moritz; Adler, Werner; Schellhaas, Barbara; Jesper, Daniel; Neurath, Markus F; Pfeifer, Lukas (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
Purpose Liver histology has prognostic relevance and is used in surveillance and therapeutic strategies. This longitudinal study was designed to evaluate the prognostic relevance of ARFI elastography in comparison to liver histology and to the FIB-4 score in a 5-year observation interval.Materials and Methods Based on the hospital database, patients with an elastography examination of the liver between 2010–2012, a liver biopsy, and a follow-up of 5 years were included in the study. The AUROCs of the events liver-related death, HCC, and liver decompensation/variceal bleeding were calculated for ARFI elastography, liver histology, and FIB-4 and compared using the DeLong test.Results In the final analysis 113 patients were included with 30 (26.5 %) patients having high-grade fibrosis and 19 (16.8 %) having liver cirrhosis in histology. The AUROC for liver-related death in the 5-year interval (9.7 %, n=11) was 0.80 [0.68–0.92] for ARFI elastography, 0.79 [0.66–0.92] for liver histology, and 0.66 [0.53–0.79] for FIB-4 with a p-value of 0.83 comparing ARFI to histology and a p-value of 0.02 comparing ARFI to FIB-4. The AUROC for liver decompensation/variceal bleeding (13.3 %, n=15) was 0.86 [0.76–0.94] for ARFI, which is significantly higher than the AUROC of liver histology with 0.71 [0.56–0.86] (p=0.02) and FIB-4 with 0.67 [0.54–0.80] (p=0.003). There was no significant difference for the event HCC when comparing ARFI to histology (p=0.33) or FIB-4 (p=0.14).Conclusion The prognostic value of ARFI elastography seems to not be inferior to liver histology regarding liver-related survival and might even outperform histology and the FIB-4 score for predicting some liver-related complications.
Keywords: ARFI elastography; liver fibrosis; liver cirrhosis; FIB-4 Score; liver histology